Near-Infrared Optical Imaging of Ovarian Cancer Xenografts with Novel α3-Integrin Binding Peptide “OA02” - Olulanu H. Aina; Jan Marik; Regina Gandour-Edwards; Kit S. Lam (Molecular Imaging)
Through screening of random one-bead one-compound (OBOC) libraries, we previously identified cyclic peptides with the cDGXGXXc motif that bind to α3 integrin subunit on ovarian adenocarcinoma cell lines ES-2, SKOV-3, and CaOV-3. We subsequently synthesized two secondary libraries based on this motif and identified new peptides that bound with a higher affinity to these cell lines. One of the peptides identified from the 20% “down-substituted” focused library was the cdG-HCit-GPQc (“OA02”) peptide. The goal of this study was to determine whether this peptide labeled with near-infrared probes could be detected after intravenous injection in ovarian tumor-bearing mice and if it would selectively localize in the tumor. Three different forms of this peptide were synthesized, “OA02”-biotin (noncovalently linked to streptavidin-Cy5.5); “OA02”-Cy5.5 and “OA02”-AlexaFluo 680. Using a KODAK IS2000MM image station, these peptide probes were used at the near-infrared (NIR) spectra to image nude mice bearing ES-2 (α3 integrin positive) and Raji (α3 integrin negative) xenografts. The peptide probe displayed highly specific tumor uptake within 15 min, which lasted for 70 min for “OA02”-Cy5.5 and “OA02”-AlexaFluo 680 and for 24 hours for “OA02”-biotin-streptavidin-Cy5.5. Some kidney and bladder signal were noted. Prior injection with anti-α3 monoclonal antibody blocked the binding of this peptide to the ES-2 tumors.